HOW DO HIGH ACHIEVER STUDENTS APPLY LEARNING STRATEGIES ON READING? - Susanti, Yunik; Mulyantama, Dwiki Ade (English Education:Journal of English Teaching and Research, 2016)
Learning strategies used by the learners to help them comprehend, learn, or retain new information and achieve learning goals easily. This research aims at finding how the students apply learning strategies in their reading activity. The goals are to find the kinds and the most frequent learning strategies on reading together with the reason of using those most frequent strategies. This case study was carried out on the high achievers third grade students of English Department University of Nusantara PGRI Kediri. The data are collecting using questionnaire ,documentation and interview . The data then analyzed using quantitative data analysis for questionnaire data andquanitative analysis for the rest. There are three points that can be discovered from this research. 1) There are six learning strategies are used by high achievers, 2) Compensation Strategy is the strategy which is the most frequently used by high achievers in solving the problems of reading. 3) High achievers students have different reasons in applying learning strategies when they get problems, it is because of interest and urgent time.Based on three finding above, students should be aware the benefit of having learning strategies during they are learning English, especially in reading.By knowing that Compensation Strategy is the most frequent strategy used, the lecturers or teachers can use teaching strategies that appropriate with this strategy, for example: in reading exercise, students are given two passages with different contexts, but using same words or phrases in some parts of passages. So, students are able to differenciate the meaning of word when they guess it in a passage.